ANALISIS YURIDIS YAYASAN YANG TIDAK MENGIKUTI KETENTUAN UNDANG-UNDANG NOMOR 28 TAHUN 2004 TENTANG YAYASAN SETELAH KELUARNYA PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA REPUBLIK INDONESIA NOMOR 2 TAHUN 2016 - ERVINA YULIA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Budiman Ginting2. Sunarmi3. T. Keizerina Devi A Based on the research results, it found out that the Foundation which has not adjusted its articles of association with Law No. 28/2004 on Foundation cannot put the word “Yayasan” before the name of the foundation and it can be liquidated based on the ruling of the District Court. The role of the notary to settle the situation of the Foundation which has not adjusted its articles of association with Law No. 28/2004 on Foundation is to make the association adjustments deed and to send notification to the Ministry of Law and Human Rights of the Republic of Indonesia by using the Administration System of Legal Entity. The obstacle encountered by the notary in the application of the Regulation of the Ministry of Law and Human Rights of the Republic of Indonesia No. 2/2016 is that in juridical view, the law has not regulated the details of the application of the foundation establishment based on the administration system of legal entity and the government has not adequately socialized the new regulations concerning foundation establishment; and in sociological view, the society do not understand and are not open minded to the explanation provided by the notary.Keywords: Foundation, Notary, Legal Entity.